(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Due to their safety and availability, medicinal plants are natural alternatives to orthodox medicines in health management, particularly in developing countries. One such plant is Boswellia dalzielii, a renowned tree in northern Nigeria that is extensively used due to its ethnomedicinal history. This study aimed to evaluate the antioxidant of some organic acids identified in the stem bark extract of B. dalzielii by Liquid Chromatography Mass Spectrometer (LCMS). The stem bark was extracted with ethanol using the cold maceration method. Antioxidant assay using 2,2-Diphenyl 1-Picryl-Hydrazyl-hydrate (DPPH), Ferric Reducing Antioxidant Property (FRAP), and Hydrogen Peroxide (H2O2) methods were used, and the results showed the highest antioxidant activity with higher concentrations of the extract; 49.580% ± 0.214, 3.540 ± 0.022 and 45.145% ± 0.234 for DPPH, FRAP and H2O2 respectively. And significantly lower than the standard (Ascorbic acid) used, 95.01 ± 0.001, 3.540 ± 0.120, and 91.390%± 0.022 respectively. the LCMS profile revealed the presence of many organic acids and other metabolites; Malonamic acid, D-pyroglutamic acid, Maleamic acid, Benzohydroxamic acid, 2-bromo-1,10-phenanthroline, p-tropoquinone (Quinone derivatives) among others. Therefore, the stem bark of B. dalzielii extract possesses antioxidant potential and could be due to its organic acid presence, it can be concluded that the stem bark of this plant may perhaps be useful in health management.